Two-channel data acquisition unit for heart sound analysis - Jamaluddin, Mohd. Najeb; Salleh, Sh-Hussain; Yusoff, Khalid (IEEE, 2005)
This paper describes the development of a data acquisition system for the electrocardiogram (ECG) and the phono-cardiogram (PCG). Diagnosing heart sounds and heart murmurs using the stethoscope is an established practice clinically. However it requires considerable experience and training, to ensure validity and reproducibility. Echocardiography provides more definitive diagnosis in this respect but it is expensive and not widely available. With the advancement in personal computers (PC), this data acquisition unit interfaces with any desktop or notebook PC and functions as a virtual instrument for the heart diagnostic system. The ECG has been a reliable reference for the cardiologists to determine the first (S1) and second (S2) heart sound. Transformation of the heart sound signal using DSP technique, that is the Instantaneous Energy (IE) and Instantaneous Frequency (IF) for heart diagnostic can be a new approach for cardiologists. Furthermore, combining phonocardiogram with ECG for online diagnosis may be an important way forward. This paper describes the development of two channel acquisition system for heart diagnostic base on DSP technique.